2014
DOI: 10.1038/bjc.2014.272
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and targeting of cellular bioenergetics: inhibition of pancreatic cancer cell proliferation

Abstract: Background:Targeting both mitochondrial bioenergetics and glycolysis pathway is an effective way to inhibit proliferation of tumour cells, including those that are resistant to conventional chemotherapeutics.Methods:In this study, using the Seahorse 96-well Extracellular Flux Analyzer, we mapped the two intrinsic cellular bioenergetic parameters, oxygen consumption rate and proton production rate in six different pancreatic cancer cell lines and determined their differential sensitivity to mitochondrial and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
94
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 50 publications
(86 reference statements)
3
94
0
Order By: Relevance
“…Because cancer cells are more dependent on glycolysis (Warburg effect), 25 there have been various attempts to block glycolysis as a strategy for inhibiting cancer cells. 8,26 A number of drugs that target mitochondrial oxidative phosphorylation in the tricarboxylic acid cycle, such as AICAR (5-aminoimidazole-4-carboxamide ribonucleotide), oxaloacetate, oligomycin, and metformin, have also been extensively tested. 27,28 In our study, rather than using specific GBM cell lines, we chose GBM-TS, as we believe new therapeutic approaches should target the subpopulation of GBM cells responsible for treatment failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because cancer cells are more dependent on glycolysis (Warburg effect), 25 there have been various attempts to block glycolysis as a strategy for inhibiting cancer cells. 8,26 A number of drugs that target mitochondrial oxidative phosphorylation in the tricarboxylic acid cycle, such as AICAR (5-aminoimidazole-4-carboxamide ribonucleotide), oxaloacetate, oligomycin, and metformin, have also been extensively tested. 27,28 In our study, rather than using specific GBM cell lines, we chose GBM-TS, as we believe new therapeutic approaches should target the subpopulation of GBM cells responsible for treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…1 Modulation of cancer cell metabolism, one of the emerging therapeutic targets proposed to overcome this limitation, is considered a promising therapeutic approach. 7 2-Deoxyglucose (2DG), which is closely related to cellular energy restriction, has been shown to inhibit cancer cell proliferation in pancreatic cancer 8 and breast cancer cell models. 9 Moreover, it has been reported that 2DG becomes a more effective anticancer agent when combined with biguanide, which inhibits mitochondrial oxidative phosphorylation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An enhanced antioxidant capacity allows cancer cells to not a universal finding, and mitochondrial respiration impairment is not a fixed feature of cancer cells [41] . Although the glycolytic inhibitors targeting the Warburg effect have been investigated in various cancer types, the glycolytic inhibitors with the exception of 3-BP (a lactate analog) [18,19, , 3-BrOP (a 3-bromopyruvate derivative) [71][72][73][74] , and dichloroacetate (DCA) have demonstrated low efficacy in arresting tumor growth when used alone [99] ; these inhibitors include 2-deoxy-D-glucose (a glucose analog) [70,[100][101][102][103][104][105][106][107][108][109][110][111][112] , lonidamine (a derivative of indazole-3-carboxylic acid) [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] , methyl jasmonate on HK , 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one on PFK [162]…”
Section: Initiation Of Metastasismentioning
confidence: 99%
“…Bioenergetic characterization of ovarian cancer cells isolated from the tumor or ascites of chemonaïve ovarian cancer patients also revealed a similar picture, confirming the presence of a metabolic heterogeneity in ovarian cancer. Variability in the bioenergetics profiles has been described in breast, sarcoma and pancreatic cancer cell lines 31,40 . A recent analysis by Dier et al of the bioenergetic dynamics and histology of 8 ovarian cancer cell lines also showed a diversity in the energy dynamics, similar to our findings.…”
Section: Discussionmentioning
confidence: 99%